Penerapan Asas In Dubio Pro Reo Terhadap Pertimbangan Hakim Dalam Putusan Nomor: 423/PID.SUS/2015/PN.DUM Tentang Perkara Perambahan Hutan - Situmorang, Poltak H; Deliana, Evi; R, Mukhlis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
A reglation or law is just a device. Law in principle must be upheld to achieve justice. Judges as the last estuary of judiciary may not only be as mouthpieces or implementers of the law alone, but judges are required to be able to make legal discoveries so that a sense of justice in society can be achieved. As in the case of the forest encroachment by the defendant Ashari, the judge is expected to be able to make legal discovery and bring justice in his decision. Based on this understanding the authors formulated three problem formulations. First, what is the basis for the judge’s judgment in issuing decisions in the case of forest encroachment. Second, how judge’s should consider in deciding cases of forest encroachment in the event of a change of law. Third, how is the application of the principle in dubio pro reo by the judge in decision Number:423/PID.SUS/PN.DUM conerning the case of forest exploitation.The type of research or problem approach that will be used in this research is normative juridical. In this normative research, law is conceptualized as what is written in the legislation (law in books) or law is conceptualized as a rule or norm which is a benchmark of human behavior that is considered appropriate.The result of this study it can be seen that the legal consideratios by the judge determine what will be the decision of the defendant. Judges is passing verdicts cant merely consider what is contained in the laws and regulatios and facts at the hearing, but also pay attentions to any values and norms that exist and live in society. This justice is not only what is felt by the people but also justice for the environment (ecological justice). When examining the case of the existing laws and regulations its not completely perfect so that it can answer every legal problem that ccurs in the communty. Because basically legislation is only one stage in the process of legal formation. So for that, the judge needs to make the next stage of legal formation through the creation or this covery of the law to answer any existing legal flaws. In passing the verdict, the judges often have doubts about aplayingthe law to the defendant, in this case the judge must decide the things that are most beneficial for accused or are called the principle in dubio pro reo. In addition, the panel of judges can apply the principle in dubio pro natura. In addition to ensuring the fulfillment of human rights for everyone who is presented before a trial, also must pay attention to aspects of environmental protection.Keywords: Judge Consideration-Decision-Legal Discovery-Principle In Dubio Pro Reo-Principle In Dubio Pro Natura